Enough is too much: the excessiveness objection to sufficientarianism. (29th July 2022) - Knight, Carl
Abstract: The standard version of sufficientarianism maintains that providing people with enough, or as close to enough as is possible, is lexically prior to other distributive goals. This article argues that this is excessive – more than distributive justice allows – in four distinct ways. These concern the magnitude of advantage, the number of beneficiaries, responsibility and desert, and above-threshold distribution. Sufficientarians can respond by accepting that providing enough unconditionally is more than distributive justice allows, instead balancing sufficiency against other considerations.